Characterization and optimization of a β detector for 18F radio-guided surgery. (April 2023) - Mirabelli, R.; Morganti, S.; Cartoni, A.; De Simoni, M.; Faccini, R.; Fischetti, M.; Giordano, A.; Scotognella, T.; Solfaroli-Camillocci, E.; Collamati, F.
Abstract: Radio-Guided Surgery (RGS) is a nuclear medicine technique to support the surgeon during surgery towards a complete tumor resection. It is based on intraoperative detection of radiation emitted by a radio-pharmaceutical that bounds selectively to tumoral cells. In the past years, an approach that exploits β − emitting radiotracers has been pursued to overtake some limitations of the traditional RGS based on γ emission. A particle detector dedicated to this application, demonstrating very high efficiency to β − particles and remarkable transparency to photons, has been thus developed. As a by-product, its characteristics suggested the possibility to utilize it with β + emitting sources, more commonly in use in nuclear medicine. In this paper, performances of such detector on 18 F liquid sources are estimated by means of Monte Carlo simulations (MC) and laboratory measurements. The experimental setup with a 18 F saline solution comprised a "positron signal" spot (a 7 × 10 mm cylinder representing the tumor residual), and a surrounding "far background" volume, that represented for the detector an almost isotropic source of annihilation photons. Experimental results show good agreement with MC predictions, thus confirming the expected performances of the detector with 18 F, and the validity of the developed MC simulation as a tool to predict the gamma background determined by a diffuse source of annihilation photons. Highlights: Radio Guided Surgery (RGS) based on β + radiation extends its range of application. This novel β -probe can detect 18F betas, with low annihilation photon background. A simulation has been developed and validated to foresee the impact of background.